Produção e purificação de nanotubos de carbono via decomposição catalítica do metano - Milanezi, Henrique Carvalhais (2024)
Carbon nanotubes (CNTs) are materials with the potential to develop disruptive technologies, such as the construction of space elevators and transistors smaller than silicon, but their production is still an engineering challenge. The catalytic decomposition of methane (DCM) is an interesting route for this, using a greenhouse gas to prepare a high value-added product while also producing COx-free hydrogen, an advantage over the commercial route via methane steam reforming. In the present work, DCM was studied in the 700 ºC to 850 ºC range using iron catalysts supported on magnesium oxide or magnesium aluminate, with the aim of understanding the dynamics of the reaction and improving the synthesis of CNTs by increasing the amount produced and reducing the presence of defects in their structure. To this end, DCM was carried out by changing some of the main process variables: support material, iron content dispersed in the support, reactor type, methane fraction in the feed, reaction temperature, residence time and reducing agent. This study exists as a continuation of the IC project supported by FAPESP (process 2021/00622-8) during which DCM was evaluated with the iron catalysts supported on magnesium oxides described here. The prepared catalysts were characterized by temperature-programmed reduction (TPR), N2 physisorption, X-ray diffraction (XRD) and transmission electron microscopy (TEM), while the catalysts after DCM were characterized by XRD, TEM, thermogravimetry (TG) and Raman spectroscopy. The catalyst with the highest yield was 40%FeMgAl2O4, with 1,04 grams of carbon per gram of catalyst, while the 2,5%FeMgAl2O4 catalyst produced 7,23 grams of carbon per gram of iron, the highest yield when weighted by metal content, while the 2,5%FeMgO catalyst was the least active of those studied. Microscopy confirmed the synthesis of carbon nanotubes as well as other structures, while Raman spectroscopy indicated the presence of nanotubes with one or two walls. The carbonaceous products with the least amount of defects came from DCM with the 10%FeMgAl2O4 catalyst when carried out at 750 ºC, with an ID/IG ratio of 0,188, which represents the ratio between defective and graphitic material. The CNTs of the 2.5%FeMgAl2O4 catalyst were estimated to have diameters of up to 8,6 nm.